PENGARUH MOTIVASI TERHADAP KINERJA PERSONEL BAGIAN SATRESKRIM POLRES PAMEKASAN YANG DIMEDIASI OLEH KOMITMEN - Chamariyah; Mohammad Kadarisman; C. Sri Hartati (Fakultas Ekonomi Universitas 45 Surabaya, 2022)
Mohammad Kadarisman, 2022. The Effect of Motivation on the Performance of Personnel of the Satreskrim Section of the Pamekasan Police Mediated by Commitment, Postgraduate Program at Wijaya Putra University. This type of research is cross-sectional, due to a certain time span/simultaneously conducting observations, recordings given by respondents. By using a quantitative approach, the research sample was 65 respondents. In this study, the data will be processed using SEM-PLS data analysis.The aims of this research are: 1). To determine the direct effect of motivation on personnel performance. 2). To determine the direct effect of motivation on personnel commitment. 3). To determine the direct effect of commitment on personnel performance. 4). To determine the indirect effect of motivation on personnel performance mediated by commitment. The results showed that: 1) Motivation had a positive and significant effect on personnel performance. This is evidenced by the original sample value and p-values ​​of 0.276 and 0.029. 2). Motivation has a positive and significant effect on commitment. This is evidenced by the original sample value and the p-values ​​of 0.546 and 0.000. 3). Commitment has a positive and significant effect on personnel performance. This is evidenced by the original sample value and p-values ​​of 0.365 and 0.004. 4). Motivation has a significant positive effect on personnel performance mediated by commitment. This is evidenced by the original sample value and p-values ​​of 0.201 and 0.026.